Finite element analysis of thick annular sector plates - Meghre, A. S.; Kadam, K. N. (Journal of Structural Engineering, 2024)
Analysis of thick annular sector plates is presented using finite element method. The element of annular sector shape has nine nodes and each node has six displacement parameters. The formulation is based on higher order plate theory, in polar coordinates, and three dimensional stress-strain relations. The element is specially derived for application to annular sector plates and hence is convenient to use compared to the available nine noded isoparametric element. The stress resultants are obtained in polar coordinates and it is easy to apply boundary conditions on curved and oblique edges. Results of plates with three different boundary conditions are presented for different a/h ratios and are expected to be useful to future workers in the field.